Sooner or later: Age at onset of generalized anxiety disorder in older adults - Gonçalves, D; Byrne, G (2012)
Background Generalized anxiety disorder (GAD) is a common disorder in older adults, with widespread and long-lasting consequences. In this study, we assessed the characteristics associated with lifetime GAD in community-dwelling adults according to their age at onset of the disorder. Methods Study sample was extracted from the 2007 National Survey of Mental Health and Well Being, a nationally representative cross-sectional survey that interviewed 8,841 Australians aged between 16 and 85 years using the Composite International Diagnostic Interview. Of the 3,178 participants aged 55-85 years, there were 227 (M = 63.7 years; 65% female) with a lifetime diagnosis of GAD who were the focus of our analyses. Results Age at onset was defined as early (<26 years) or late (≥26 years), based on the median age at onset for the entire sample. The weighted prevalence estimates for 12-month and lifetime GAD were 2.8% (95% CI: 2.0, 3.7) and 7.0% (95% CI: 5.7, 8.3), respectively, with less than one-tenth of the participants being diagnosed after the age of 60 years. Having the first GAD episode earlier in life was significantly associated with physical abuse during childhood (OR = 0.34, 95% CI: 0.16, 0.75), lifetime diagnosis of dysthymia (OR = 0.34, 95% CI: 0.18, 0.67), and number of GAD episodes (OR = 0.29, 95% CI: 0.14, 0.58), after adjusting for current age and 12-month GAD. Conclusion In older adults, an earlier age at onset of GAD was associated with childhood physical abuse and worse clinical outcomes, thus appearing to be a marker for increased vulnerability to GAD. © 2011 Wiley-Liss, Inc.